Face-to-face and online collaboration: appreciating rules and adding complexity. (1st January 2002) - Noss, Richard; Hoyles, Celia; Gurtner, Jean-Luc; Adamson, Ross; Lowe, Sarah
This paper reports how 6-8 year-old children build, play and share videogames in an animated programming environment. Children program their games using rules as creative tools in the construction process. While working both face-to-face and remotely on their games, we describe how they can collaboratively come to explain phenomena arising from programmed or "system" rules. Focusing on one illustrative case study of two children, we propose two conjectures. First, we claim that in face-to-face collaboration, the children centre their attention on narrative, and address the problem of translating the narrative into system rules which can be "programmed" into the computer. This allows the children to debug any conflicts between system rules in order to maintain the flow of the game narrative. A second conjecture is that over the internet children are encouraged to add complexity and innovative elements to their games, not by the addition of socially-constructed or "player" rules but rather through additional system rules which elaborate the mini-formalism in which they engage. This shift of attention to system rules occurs at the same time, and perhaps as a result of, a loosening of the game narrative that is a consequence of the remoteness of the interaction.